(untitled) (Indian Journal of Public Health Research & Development, 2020)
The present study examined to investigate the influence of self-efficacy on student engagement of Senior Secondary School students. The respondents were students from senior secondary school of Jammu and Kashmir. A Sample of 400 senior Secondary School Students (200 boys and 200 girls) were selected from Jammu and Kashmir by employing simple random sampling. T-test, correlations and regression were employed to analyze the data. The study indicated that (a) there exists significant difference between senior Secondary School boys and girls with their self-efficacy (b) there exists Significant Difference Between Private and Government senior Secondary school Students with their self-efficacy (c) there exists Significant Difference Between senior Secondary School Boys And Girls with their student engagement (d) there exists significant difference between private and government senior Secondary school Students with their student engagement. It revealed that significant relationship was found between self-efficacy and student engagement of senior secondary school students. It also found the self-efficacy had significant influence on student engagement of senior Secondary School Students.